Ethanol production in the United States: The roles of policy, price, and demand. (February 2022) - Newes, Emily; Clark, Christopher M.; Vimmerstedt, Laura; Peterson, Steve; Burkholder, Dallas; Korotney, David; Inman, Daniel
Abstract: Assessments of the impact of the U.S. renewable fuel standard (RFS) should inform consideration of future biofuels policy. Conventional wisdom suggests the RFS played a major role in stimulating the ten-fold expansion in ethanol production and consumption in the United States from 2002 to 2019, but evidence increasingly suggests the RFS may have had a smaller effect than previously assumed. Price competitiveness, federal and state policies such as reformulated gasoline requirements, and octane content in ethanol also affect ethanol market attractiveness. This study explores the roles of policy and economic factors by comparing historical data with results from scenarios simulated in a system dynamics model. Results suggest price competitiveness may explain much of the growth in the ethanol industry from 2002 to 2019. The Volumetric Ethanol Excise Tax Credit and phaseout of the oxygenate methyl tert-butyl ether contributed to earlier growth relative to expected timing of growth based on fuel price alone. The RFS (modeled through observed Renewable Identification Numbers) contributed to increased ethanol production in later years and may have increased production in the earlier years if risk of investment was decreased by the RFS Program. Highlights: Competitive U.S. ethanol price is the main driver for ethanol expansion 2002–2019. Policies accelerated and increased ultimate ethanol production. The U.S. renewable fuel standard increased production by up to two billion gallons. Simulation is a valuable framework for estimating economic value and policy impact.